SEMNALĂRI NOI ÎN GRUPUL PEDERINELOR (COLEOPTERA, PAEDERINAE, STAPHYLINIDAE) DIN REPUBLICA MOLDOVA - Mihailov, Irina (CEP USM, 2023)
In the paper are presented two new species from the subfam. Paederinae (order Coleoptera, family Staphylinidae) found in the natural habitats of the Republic of Moldova. 1. Medon piceus (Kraatz, 1858), a species with eurytopic distribution, populates forest areas, appearing sporadically. 2. Astenus discopunctatus (Say, 1831), adventive species, detected in the oak forest litter mixed with hornbeam. For each species are described, the collection points, status, morphological features, geographical distribution, accentuation of the bioecological category, the place of maintenance in the collection: Coleoptera, Staphylinidae.

The present communication analyzes the most representative postures of laughter, the humorous, ironic expressions uttered by the literary characters from the novel Moromeții (vol. I) by Marin Preda, in various family contexts or existential conflicts. The smile and specific way of laughing of each character outlines his moral, psychological portrait, highlighting, at the same time, the importance and semantic role of such an affective reaction.
MIHAILOV, Irina. Semnalări noi în grupul pederinelor (coleoptera, paederinae, staphylinidae) din Republica Moldova. In: Plant Protection - Achievements and Perspectives: scientific international symposium, Chisinau, October 2-3, 2023. CEP USM, 2023. pp.63-67. ISBN 978-9975-62-563-0. DOI: https://doi.org/10.53040/ppap2023.09.
Keywords: subfam. Paederine; Staphylininae; fam. Staphylinidae; Coleoptera; Medon piceus; Astenus discopunctatus; new species